2022
DOI: 10.1101/2022.08.08.503214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Auditory corticofugal neurons transmit auditory and non-auditory information during behavior

Abstract: Layer 5 pyramidal neurons of sensory cortices project corticofugal axons to myriad of sub-cortical targets, thereby broadcasting high-level signals important for perception and learning. Recent studies suggest dendritic Ca2+ spikes as key biophysical mechanisms supporting corticofugal neuron function: These long-lasting events drive burst firing, thereby initiating uniquely powerful signals to modulate sub-cortical representations and trigger learning-related plasticity. However, the behavioral relevance of co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 127 publications
1
4
0
Order By: Relevance
“…In L2/3 and L4, only 11% of RS units exhibited significant spike rate modulation during spontaneous facial movements (all positively modulated), whereas 26% of units in L5 and L6 were significantly modulated (17% positively modulated), (Figure 6C-D). A more granular analysis of spike rate modulation by depth confirmed prior reports that deep layer auditory cortex (ACtx) neurons are more strongly recruited by movement (Figure 6E) [32][33][34][35].…”
Section: Suppressing Auditory Cortex Neural Activity Enhances Sound-e...supporting
confidence: 81%
“…In L2/3 and L4, only 11% of RS units exhibited significant spike rate modulation during spontaneous facial movements (all positively modulated), whereas 26% of units in L5 and L6 were significantly modulated (17% positively modulated), (Figure 6C-D). A more granular analysis of spike rate modulation by depth confirmed prior reports that deep layer auditory cortex (ACtx) neurons are more strongly recruited by movement (Figure 6E) [32][33][34][35].…”
Section: Suppressing Auditory Cortex Neural Activity Enhances Sound-e...supporting
confidence: 81%
“…One potential candidate is the massive system of descending auditory cortical projections. Indeed, auditory cortico-collicular neurons preferentially target the non-lemniscal shell IC layers (Bajo et al, 2007; Winer, 2005; Yudintsev et al, 2021), and are highly active during the response period in a similar instrumental task to the one employed here (Ford et al, 2022). However, auditory cortex lesions apparently reduce, but do not abolish putative non-auditory activity in cortico-recipient IC neurons (Lee et al, 2023), suggesting that shell IC neurons could inherit task-relevant activity from non-cortical sources.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, observing topographical CC activity patterns in a behavioral (possibly learning-related) context might be the only way to definitively describe their role in providing frequency-specific feedback to the IC. Ford et al (2022) imaged activity in dendrites of CC neurons during behavior and concluded that they contribute to learning by transmitting non-auditory signals. However, they did not report on topographical aspects.…”
Section: Discussionmentioning
confidence: 99%